10.61533 PENGARUH KUALITAS PELAYANAN TERHADAP MINAT NASABAH DALAM MENGGUNAKAN MOBILE BANKING DAN INTERNET BANKING (Studi Kasus Pada PT. Bank Central Asia Tbk KCU Pangkalpinang Tahun 2024) - Erichson, Christian; Shinta Lestari, Deara; Zamhari (STIE IBEK Pangkalpinang, 2024)
This study seeks to examine the impact of customer interest in utilizing mobile banking and internet banking services from four perspectives: service aspects, customer understanding aspects, target accuracy aspects, and timeliness aspects. The case study is conducted at PT. Bank Central Asia Tbk KCU Pangkalpinang in 2024. The study employs a survey method using a questionnaire as the primary data collection tool. The sample includes 100 customers of BCA Bank KCU Pangkalpinang who utilize mobile banking and internet banking services. Data analysis is performed through multiple linear regression to investigate the relationship between the independent variables (service aspects, customer understanding aspects, target accuracy aspects, and timeliness aspects) and the dependent variable (customer interest in using mobile banking and internet banking). The findings of the study reveal that the service aspect has a partial impact on customer interest in using mobile banking and internet banking. Similarly, the customer understanding aspect, target accuracy aspect, and timeliness aspect each partially influence customer interest in these services. When considered together, the service quality variables—comprising the service aspect, customer understanding aspect, target accuracy aspect, and timeliness aspect—have a positive and significant effect on customer interest in using mobile banking and internet banking.